Swab and Sputum SARS-CoV-2 RNA-Negative, CT-Positive, Symptomatic Contacts of COVID-19 Cases: A Hypothesis-Generating Prospective Population-Based Cohort Study of Eight Clusters - Huang, Lei; Zhang, Xiuwen; Zhang, Lingli; Xu, Jingjing; Wei, Zhijian; Xu, Yuanhong; Zhang, Chengyuan; Xu, Aman (Frontiers in Medicine, 2021)
Background: While some contacts of COVID-19 cases become symptomatic and radiographically abnormal, their SARS-CoV-2 RNA tests remain negative throughout the disease course. This prospective population-based cohort study aimed to explore their characteristics and significances. Methods: From Jan 22, 2020 until Jul 3, a total of 14,839 people in Feidong, China with a population of ~1,081,000 underwent SARS-CoV-2 RNA testing, where 36 cases (0.2%) with confirmed COVID-19 infection (Group-1) and 27 close contacts (0.2%) testing negative for SARS-CoV-2 RNA but having both positive COVID-19 exposure histories and radiological findings (Group-2) from 8 clusters were prospectively identified. Another 62 non-COVID-19 pneumonia cases without any exposure history (Group-3) were enrolled, and characteristics of the 3 groups were described and compared. Results: Fever was more common in Group-2 than Groups-1 and 3. Median leucocyte, neutrophil, monocyte, and eosinophil counts were all lower in Groups-1 and 2 than Group-3. Total protein and albumin levels were higher in Groups-1 and 2 than Group-3. C-reactive protein level was lower and erythrocyte sedimentation rate slower in Groups-1 and 2 than Group-3. Median duration from illness onset to discharge was longer in Group-1 (27 d) than Groups-2 and 3 (both 17 d). Among contacts of a confirmed COVID-19 patient, 1 patient with negative virus RNA tests but positive symptoms and radiological findings transmitted COVID-19 to another case. Conclusions: Among close contacts of confirmed COVID-19 cases, some present with positive symptoms and CT findings but test negative for SARS-CoV-2 RNA; they have features more similar to confirmed COVID-19 cases than non-COVID-19 pneumonia cases and might have transmitted SARS-CoV-2 to others. Such cases might add to the complexity and difficulty of COVID-19 control. Radiological examination might need to be conducted for symptomatic SARS-CoV-2 RNA-negative contacts of COVID-19 cases. Our hypothesis-generating study might suggest that SARS-CoV-2 RNA testing by rRT-PCR assays of common respiratory (throat swab and sputum) specimens alone, the widely accepted “golden standard” for diagnosing COVID-19, might be sometimes insufficient, and that further studies with some further procedures would be warranted for the SARS-CoV-2 RNA negative, radiographically positive, symptomatic contacts of COVID-19 cases, to further reveal their nature.